Elastic Stable Titanium Flexible Intramedullary Nails Versus Plates in Treating Low Grade Comminuted Femur Shaft Fractures in Children. Issue 4 (28th August 2019) - Luo, Yi; Wang, Lin; Zhao, Li‐hua; Wang, Yi‐cheng; Chen, Meng‐jie; Wang, Sun; Ma, Qi‐chao
Abstract : Objectives: To review the experience at our center with elastic stable titanium flexible intramedullary nails (ESIN) for pediatric femoral shaft unstable fractures. Methods: From January 2015 to January 2017, 56 consecutive patients with femur shaft fractures were treated in our hospital. History and radiologic parameters were retrospectively reviewed. The inclusion criteria were: femur shaft fractures treated by ESIN or locking compressing plates (LCP); more than 2 years' follow‐up care; and complete clinical information. A total of 51 patients were included according to the criteria: 16 girls and 35 boys. Ages at operation averaged 5.9 ± 2.8 years. Outcome: anteroposterior (AP) and lateral X‐ray radiographs were performed every 2 weeks before the fracture healing, every 3 months until 1 year, then once a year after the surgery. Clinical examinations were recorded for any clinical deformity, hardware prominence, pain, and infection. ESIN were applied in either a retrograde or an antegrade fashion for 29 patients. For 22 patients, LCP were implanted. For the remaining 5 cases, instruments other than ESIN and LCP were applied. Results: The average follow‐up time was 29 months (range, 24–37 months). The average operation time was 78.2 min (range, 25–155 mins). The average blood loss in surgery was 69.6 mL (range, 3–700 mL). The average healing of fracture time was 2.2 month (range, 1–6 months). The average removal of implants time was 7.8 months (range, 3–20 months). The average expense for index operation was CNY 31 100 (CNY 17 500–142 200). Comminution grades were strongly correlated with time to fracture union ( P  < 0.001, r = 0.53) and time to implant removal ( P = 0.006, r = 0.38). For comminuted pattern, the operation time and blood loss during operation in LCP were significantly higher than those in ESIN ( P = 0.037 and P = 0.006, respectively). Other clinical parameters were similar between the two groups. No clinically detectable LLD, rotational or angular deformity was found. All patients recovered full knee range of motion. In this series, 30 patients (59%) had complications; 26 minor complications (51%) did not require unplanned surgery, most of which were prominence of hardware; 4 patients (8%) had a major complication and underwent an unplanned surgery. Of these, 2 were refractures distal to primary fracture and 2 were intolerable prominence of ESIN. Conclusions: Elastic stable intramedullary nails provide equivalent outcomes but decreased operative time and blood loss during surgery, and lower hospitalization cost in treating low‐grade comminuted femur shaft fracture compared with plating techniques. The results of this study support the use of ESIN over plates in low‐grade comminuted femur shaft fractures despite the fact that both options are indicated.